2014
DOI: 10.1352/1934-9556-52.4.282
|View full text |Cite
|
Sign up to set email alerts
|

Empirically Derived Model of Social Outcomes and Predictors for Adults With ASD

Abstract: This study used data from the National Core Indicators (NCI) Survey to derive an empirically validated measurement model for social outcomes and associated constructs for both individuals with Autism Spectrum Disorder (ASD) and individuals with other disabilities. Items consistent with the survey structure of the NCI were selected as initial indicators of the latent constructs Social Relationships, Community Inclusion, and Opportunity for Choice in factor analyses. Results yielded a novel factor structure that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…With a significant focus in the literature on loneliness, isolation, and friendship quality in autistic adults, the current study provides some initial support to think more broadly about the context of where social participation and interactions take place and the meaning ascribed. These findings may provide more context to past research by Mehling and Tasse ( 2014 ), who found that individuals with and without autism were participating in the community at similar rates but those with autism reported lower levels of friendship, implying these community interactions were not leading to increased friendships for autistic adults. In conjunction with the current findings, it is possible that autistic adults are socially participating and active in their communities, but it may not extend to the level of a close friendship.…”
Section: Discussionsupporting
confidence: 63%
“…With a significant focus in the literature on loneliness, isolation, and friendship quality in autistic adults, the current study provides some initial support to think more broadly about the context of where social participation and interactions take place and the meaning ascribed. These findings may provide more context to past research by Mehling and Tasse ( 2014 ), who found that individuals with and without autism were participating in the community at similar rates but those with autism reported lower levels of friendship, implying these community interactions were not leading to increased friendships for autistic adults. In conjunction with the current findings, it is possible that autistic adults are socially participating and active in their communities, but it may not extend to the level of a close friendship.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, examination of effects of programs such as in this study is warranted. Constructs useful to for study include social determination, social participation and relationships and personal control (Mehling & Tasse' ).…”
Section: Discussionmentioning
confidence: 99%
“…‘Best friend’ was the concept used to identify a friendship that was particularly close/strong, as subjectively understood by respondents. This item was one of five questions used by Mehling and Tassé (2014) as indicators of overall quality of social relationships, in an analysis of the National Core Indicator (NCI) Survey. The concept of a best friend confers a particular exclusivity and strength in comparison to other friendships (Branje et al, 2007) and is important enough that the lack of such a friend may be considered a deficit in developing adolescents (Richey & Richey, 1980) and associated with increased risk including loneliness (Rubin et al, 2007); while close or strong friendships have also been highlighted as important by people with intellectual disability (Robinson et al, 2018; Sigstad, 2017).…”
Section: Methodsmentioning
confidence: 99%